Implementasi Konsep Ta’dib, Ta’lim dan Tarbiah dalam Kegiatan Mondok Akhir Pekan Madrasah Ibtidaiyah Berbasis Madrasah Padang Panjang - Prasetyo, Yudo Indra; Damri, Damri; Misrawani, Misrawani; Amra, Abhanda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Religious education is also very important for a person to know the God who created it, without religious education, a person can live like an animal without the limitations of rules. However, along with the development of the times and technological advances, the value of Islamic education is fading in society. The type of research used is qualitative descriptive. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the analysis show that the application of the three concepts of Islamic education - Ta'dib, Ta'lim, and Tarbiyah is realized in every activity in the madrasah. The concept of Ta'dib is reflected in madrasah regulations which include manners and ethics, the concept of Ta'lim is contained in formal educational activities, while the concept of Tarbiyah is manifested in various motor activities of students and madrasah services to them. Weekend activities, the application of the three Islamic education concepts was also seen. The concept of Ta'dib is applied through regulations that regulate manners during mondok activities, the concept of Ta'lim is applied through the learning of students in activities, and the concept of Tarbiyah is manifested in madrasah services to meet the needs of students during weekend mondok activities